2007
DOI: 10.1007/s00227-007-0785-y
|View full text |Cite
|
Sign up to set email alerts
|

Microscale genetic differentiation in a sessile invertebrate with cloned larvae: investigating the role of polyembryony

Abstract: Microscale genetic diVerentiation of sessile organisms can arise from restricted dispersal of sexual propagules, leading to isolation by distance, or from localised cloning. Cyclostome bryozoans oVer a possible combination of both: the localised transfer of spermatozoa between mates with limited dispersal of the resulting larvae, in association with the splitting of each sexually produced embryo into many clonal copies (polyembryony).We spatially sampled 157 colonies of Crisia denticulata from subtidal rock ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 53 publications
0
21
1
Order By: Relevance
“…2), which detected the formation of pedigree structures. In contrast, clonality, which often contributes to the strong SGS at very small scales (Pemberton et al 2007, Miller & Ayre 2008, was irrelevant in Scopalina lophyropoda, since both the genet and the ramet analyses gave similar results.…”
Section: Spatial Population Structurementioning
confidence: 91%
See 1 more Smart Citation
“…2), which detected the formation of pedigree structures. In contrast, clonality, which often contributes to the strong SGS at very small scales (Pemberton et al 2007, Miller & Ayre 2008, was irrelevant in Scopalina lophyropoda, since both the genet and the ramet analyses gave similar results.…”
Section: Spatial Population Structurementioning
confidence: 91%
“…corals, bryozoans and ascidians) by using autocorrelation statistics (e.g. McFadden & Aydin 1996, Miller 1998, Pemberton et al 2007, Miller & Ayre 2008. Although sponges are common components of marine systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence of self-seeding has been found in this species for the FGB (Brazeau et al 2005). It is possible that other factors may have influenced our observations of fine-scale genetic structure, including kin aggregation (Veliz et al 2006), polyembryony (Pemberton et al 2007), and selection (Zvuloni et al 2008). We cannot rule out any of these explanations; all of them, however, require additional factors beyond our suggestion of low dispersal with limited larval mixing to produce the observed patterns.…”
Section: Discussionmentioning
confidence: 76%
“…Several circumstances have been suggested that should favour the evolution and maintenance of polyembryony in animals, but most of these do not seem applicable to algae, plants, or colonial animals, such as cyclostome bryozoans, that mate at a distance by the remote transfer of male gametes (see Pemberton et al 2007). More applicable explanations envisage polyembryony as making 'the best of a bad job' in the face of constraints on mating opportunities (Craig et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Data from a study of Crisia denticulata failed to support a suggestion by Ryland (1996) that polyembryony might be a response to limited gene flow in sessile species in which 'potential mates will differ little, and sexual reproduction may produce larvae with genotypes no less fit within the immediate vicinity than their parent'. A large proportion of the total genetic variability encompassed by 2 widely separated populations of C. denticulata was present within patches of colonies in small-scale rock overhangs (Pemberton et al 2007); thus, potential mates would not be genetically similar. Ryland (1996) also predicted (echoing an earlier suggestion made for red algae with aflagellate gametes by Searles 1980) that low sperm output from typically small cyclostome colonies, when combined with a sparse adult distribution, gave a low probability that a colony could capture enough sperm to fertilise all the eggs it could potentially produce.…”
Section: Introductionmentioning
confidence: 99%